Grain size analysis of IODP Site 303-U1307 - Isabela Moreno Cordeiro Sousa; Claude Hillaire-Marcel; Anne de Vernal; Jean-Carlos Montero-Serrano; Aurélie Marcelle Renée Aubry (PANGAEA, 2024)
This dataset consists of analyses of a Pliocene interval at Integrated Ocean Drilling Program (IODP) site 303-U1307. The site is located on Eirik Drift and was cored in 2004. The grain-size data consists of 51 samples measured in a Malvern-Panalytical Mastersizer 3000 particle-size analyzer equipped with a Hydro LV module. All data were generated in 2023. The timespan of the data set is from ~2.9 Ma to 3.2 Ma (~300 ka total duration), which covers the mid-Pliocene Warm Period (mPWP; 3.025-3.264 Ma) with an average sampling resolution of ~4 ka.